Comparison of femoral block and adductor canal block in the postoperative analgesia of patients undergoing arthroscopic knee surgery - Kucur Tülübaş, Evrim; Bostancı, İpek and Sertçakacılar, Gökhan and Pektaş, Yaser and Edipoğlu, Erdem (The European Research Journal, 2019)
Objectives: The aim of the study was to compare adductor canal block and femoral nerve block in the postoperative analgesia of patients undergoing elective arthroscopic knee surgery with respect to opioid use and Visual Analogue Scale (VAS), which is a unidimensional measurement of pain intensity. Method: The study was designed and conducted prospectively between April 2016 and November 2016 in a tertiary care hospital but the results were evaluated retrospectively. Prior to the induction of general anesthesia for knee surgery, (the first) 20 consecutive patients underwent femoral nerve block, and (the second) 20 consecutive patients received adductor canal block. Patients receiving adductor canal block for analgesia were referred to as Group A and patients receiving femoral nerve block for analgesia were defined as Group F. Pain was evaluated using the VAS score.The results were compared statistically. Results: Both the femoral nerve block and adductor canal block groups showed similar results in terms of VAS and opioid use (p < 0.05). Conclusion: In the postoperative analgesia of patients undergoing elective arthroscopic knee surgery, no difference was found between adductor canal block and femoral nerve block in terms of opioid use and VAS scores.